2020
DOI: 10.1111/ejn.14720
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation and depression: A review

Abstract: Some recent clinical and preclinical evidence suggests that neuroinflammation is a key factor that interacts with the three neurobiological correlates of major depressive disorder: depletion of brain serotonin, dysregulation of the hypothalamus-pituitaryadrenal (HPA) axis and alteration of the continuous production of adult-generated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
407
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 675 publications
(428 citation statements)
references
References 241 publications
(284 reference statements)
14
407
0
7
Order By: Relevance
“…This boosts for example vaccine responses and post-operative recovery but can also contribute to the fatal effects of a cytokine storm ( Kempuraj et al, 2020 ). Moreover, psychological states that are associated with repeatedly high stress states such as depression or PTSD are also associated with a chronic low-grade increase of these cytokines ( Speer et al, 2018 ; Troubat et al, 2020 ). Vice versa, cytokines produced in response to an inflammatory challenge can affect the HPA, closing a vicious cycle ( Straub et al, 2011 ).…”
Section: Lasting Psychosocial Stress Exposure Has a Negative Impact Omentioning
confidence: 99%
“…This boosts for example vaccine responses and post-operative recovery but can also contribute to the fatal effects of a cytokine storm ( Kempuraj et al, 2020 ). Moreover, psychological states that are associated with repeatedly high stress states such as depression or PTSD are also associated with a chronic low-grade increase of these cytokines ( Speer et al, 2018 ; Troubat et al, 2020 ). Vice versa, cytokines produced in response to an inflammatory challenge can affect the HPA, closing a vicious cycle ( Straub et al, 2011 ).…”
Section: Lasting Psychosocial Stress Exposure Has a Negative Impact Omentioning
confidence: 99%
“…The relation between inflammation and depression has been a topic of increased interest since the late 1990s, following evidence that immune challenges can induce depressive-like "sickness behaviour" and that rapid onset of MDD can be an adverse effect of interferon therapy. After presenting the main players of brain immunity, Troubat et al (2020) discussed how neuroinflammation interacts with three neurobiological correlates of MDD: monoamine depletion, the endocrine hypothalamus-pituitary-adrenal (HPA) axis and neurogenesis. A research article from Nothdurfter et al (2019) further showed in depressed patients that the pro-inflammatory cytokine interleukin 17 might be a biomarker of treatment resistance in MDD.…”
Section: Depression In Focus: Insights From Animal and Human Data Frmentioning
confidence: 99%
“…After presenting the main players of brain immunity, Troubat et al. (2020) discussed how neuroinflammation interacts with three neurobiological correlates of MDD: monoamine depletion, the endocrine hypothalamus–pituitary–adrenal (HPA) axis and neurogenesis. A research article from Nothdurfter et al.…”
mentioning
confidence: 99%
“…Depression represents the major burden of disease in Europe (Andlin-Sobocki et al, 2005) and the constellation of mood alterations associated with depression can be recapitulated in animal models repeatedly exposed to different stressors (de Kloet et al, 2005;Berton et al, 2012). The use of animal models converges with imaging studies to identify modifications of different brain regions, such as the hippocampus, prefrontal, and limbic cortices, that are associated with mood dysfunction (de Kloet et al, 2005) and provide compelling evidence for the involvement of neuroinflammation (Rial et al, 2016;Deng et al, 2020;Troubat et al, 2021) and of synaptic dysfunction (Duman and Aghajanian, 2012;Vose and Stanton, 2017) as key processes in the etiology of major depression. However, the identification of molecular systems that may be targeted to correct depressive symptoms has still failed to yield novel and effective anti-depressants (Ménard et al, 2016).…”
Section: Introductionmentioning
confidence: 99%